2019
DOI: 10.3390/v11121084
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Foamy Virus: Shared and Unique Molecular Features In Vitro and In Vivo

Abstract: The retroviral subfamily of Spumaretrovirinae consists of five genera of foamy (spuma) viruses (FVs) that are endemic in some mammalian hosts. Closely related species may be susceptible to the same or highly related FVs. FVs are not known to induce overt disease and thus do not pose medical problems to humans and livestock or companion animals. A robust lab animal model is not available or is a lab animal a natural host of a FV. Due to this, research is limited and often focused on the simian FVs with their we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 148 publications
1
32
0
Order By: Relevance
“…In BFV, free and mixed grazing of cattle and deer in rural areas may lead to BFV transmission as has been well documented for small ruminant lentiviruses in France by Erhouma and others [30], where close contact between wild ibex and goats at pastures led to small ruminant lentiviruses infections in wild animals, or for BoHV-1 which was detected in cervid populations in Germany and in Poland [24,42]. BFV transmission through saliva has been described as the most frequent route of transmission in natural conditions [3,10]; however, our own studies showed that the isolation of BFV from saliva is possible only from a small percentage of animals [32]. Unpublished data also showed that, in contrast to SFV or FFV, BFV viral load in the saliva of naturally and experimentally infected cows is very variable, from quite high to undetectable in some BFV-positive animals, but the explanation for this phenomenon is still unclear.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In BFV, free and mixed grazing of cattle and deer in rural areas may lead to BFV transmission as has been well documented for small ruminant lentiviruses in France by Erhouma and others [30], where close contact between wild ibex and goats at pastures led to small ruminant lentiviruses infections in wild animals, or for BoHV-1 which was detected in cervid populations in Germany and in Poland [24,42]. BFV transmission through saliva has been described as the most frequent route of transmission in natural conditions [3,10]; however, our own studies showed that the isolation of BFV from saliva is possible only from a small percentage of animals [32]. Unpublished data also showed that, in contrast to SFV or FFV, BFV viral load in the saliva of naturally and experimentally infected cows is very variable, from quite high to undetectable in some BFV-positive animals, but the explanation for this phenomenon is still unclear.…”
Section: Discussionmentioning
confidence: 91%
“…Most known FVs are highly prevalent in their hosts. For instance, the prevalence of BFV among cattle ranges between 7% and 50% of cattle worldwide, while in Poland it reaches over 30% (see for summary [10]). Transmission of BFV is suggested to occur through saliva, and, therefore, there is likely to be a risk of its spread through shared grazing areas or direct social or environmental contacts [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foamy viruses (FV), or spumaretroviruses, comprise five genera of the Spumaretrovirinae [11]. FVs are characterized by several unique features in their molecular biology and replication strategy compared to the Orthoretrovirinae encompassing the remaining majority of the retrovirus family including the deltaretrovirus BLV [11][12][13][14][15]. Due to their apathogenicity, broad range of susceptible host cells, and other features, FVs are promising candidates for novel virus vectors [16].…”
Section: Introductionmentioning
confidence: 99%